Coconut husk as potential sources for silica production - Anuar, Muhammad Fahmi; Yap, Wing Fen; Mohd Zaid, Mohd Hafiz (2018)
Silica can be extracted from agriculture waste. In this study, the waste coconut husk (CH) burned in controlled environment inside electrical furnace at temperature of 700 °C. These ashes were chemically treated by using two different methods of extracting silica. XRF analysis of coconut husk ash revealed that the content of SiO2 varies between 8-11 % and increased up to 90 % after chemical treatment. XRD analysis indicates that silica obtained after acid treatment was in crystalline state while by using alkali treatment it was in amorphous state.